Representations of Euro-Asian relations in 2010: South Korean newspapers report on ASEM and German newspapers on Asia (especially China) - Sommerauer, Yvonne (2014)
Empirical studies of EU-East Asian relationships as depicted in the media are increasingly moving into the foreground of discursive international relations analysis concentrated on the ASEM process. Yet region-to-region perceptions are still largely conceived within national, historical and linguistic prisms which are only gradually transferring into trans-regional ones. This working paper considers two interrelated moments, as indicated in the title, and hopes to make a modest contribution to the academic study of the construction of perceptions as a necessary precondition of and complement to an emerging sense of a common, shared and mutually beneficial inter-regional cooperation.